A Bypassing Technique for the Remedy of Portal Hypertension through Extra Hepatic Portal Vein Obstruction by CFD Analysis - Atkar, Mst Khorseda; Islam, Md Tajul (GANIT: Journal of Bangladesh Mathematical Society, 2018)
Extra-hepatic portal vein obstruction (EHPVO) is the blockage to the flow of blood in the portal vein before reaches to the liver. EHPVO is the common cause of portal hypertension in children in the most Asian countries. Examination reveals that the presence of block in the main portal vein may be responsible for the shrinkage of vein with manifold pernicious complication. The “shunt” policy is a fruitful source of restoration of the hepatic portal flow. This study shows that a new approach of bypassing (or shunting) to the blocked (thrombosed) region of the portal vein is a significant way of reducing portal hypertension and restoration of blood circulation. We studied EHPVO case through computational fluid dynamics (CFD) analysis by considering partial block formation and side to side shunt scheme inside the main portal vein. The constitutive equation for non-Newtonian fluidand energy equation are solved by control volume technique. Our study reveals that the shunting technique is strongly effective for the reconstitution of portal venous flow to the liver with lower tissue stress and rapid regression of clinical signs of portal hypertension. This new technique may potentially applicable for medication of EHPVO when shunting procedures are indicated. GANIT J. Bangladesh Math. Soc.Vol. 38 (2018) 89-104